Evaluasi User experience Pada Aplikasi Mobile Asphalt 9: Legends Menggunakan Cognitive Walkthrough dan Heuristic Evaluation - Ahmad Fahrurrozi; Satrio Hadi Wijoyo; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Asphalt 9: Legends is a racing game that shows sophisticated cars in row that play with more clear graphic. Asphalt 9: Legends has 10 millions users, but this game was found a problem from the respondent like function from the fitur such as Settings and Restart that are difficult to find for the user. Based on observation from a writer, this game has many kinds of problem such as Hidden, is a clearance symbol that shows for fitur function and feedback, which is not serving mode touchdrive function in the game so there is no feedback between the system and users. The purpose of this observation are for evaluating users interface from Asphalt 9: Legends using cognitive walkthrough and Heuristic Evaluation method. Cognitive Walkthrough method involves 4 respondents who are new users of this game, for heuristic evaluating method involves 9 evaluator experts. The result of the Cognitive Walkthrough shows the Asphalt 9: legends has enough problems in Users and Hidden. Evaluating using heuristic method shows this game has 26 usability problems which is heuristic MA01 (visibility of System Status) prinsiple has the highest problem 30.7%, meanwhile the highest average level of severity is in the Heuristic Ma03 (User Control and Freedom) principle is 2.63 in percentage.